WOMEN AS STAKEHOLDER IN PEACEMAKING AND SECURITY IN NIGERIA: EFFORTS TOWARDS ACHIEVING NATIONAL DEVELOPMENT - Obuzor, Mezewo Emerinwe; Nwabueze Emeodu, Elijah (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study investigates the underutilized yet significant role of women in peacemaking and security processes in Nigeria, focusing on their contributions as mediators, community leaders, and peacebuilders in conflict resolution and national development. Method: Utilizing J. Ann Tickner’s feminist security theory as the theoretical framework, the study adopts a qualitative approach through thematic content analysis of secondary sources, including published and unpublished academic literature. Results: Findings reveal that while women possess unique capabilities to address the social and economic dimensions of conflict, cultural, religious, and societal norms continue to marginalize them from formal decision-making in peace and security efforts. The research underscores the necessity of incorporating women into official peace negotiations and security frameworks to achieve more inclusive and sustainable conflict resolution outcomes. Novelty: This paper contributes original insight by contextualizing feminist security theory within the Nigerian peace-building landscape and highlighting the transformative potential of women's inclusion in national security strategies. It recommends institutional mechanisms and quota-based representation to ensure women's active participation in security and peacemaking processes at all governance levels.